Etnomatematika Permainan Kelereng Sebagai Teknik Belajar Matematika Sekolah Dasar - Nita Silfiana; Wahyuning Widyastuti (Islamic Elementary School Teacher Education Study Program, Faculty of Education and Teacher Training, K.H. Abdurrahman Wahid Pekalongan State Islamic University, Indonesia, 2021)
Ethnomatmatics is a culture in which there is a concept of math. The existence of such a culture has a very important influence for mathematics learning. The purpose of this research is to know and explain about the mathematical elements contained in marble games and their use in context of mathematics learning. This study uses literature studies. The result of this study is to know that in the game of marbles there is an ethnic mathematics related to geometric concept,e.g. circles, balls, triangles, and distances. The concept of marbles is used to introduce and provide an understanding of the concept of geometry and distance through local cultural games.